Pengaruh Metode Silaba Terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 SDN 68 Palembang - patma, patmapuspitasari; Ilham Arvan Junaidi; Imelda Ratih Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formulation of the problem in this research is: is there an influence of the syllable method on the early reading abilities of first-grade students at SD Negeri 68 Palembang? The purpose of this research is to determine the effect of the syllable method on the early reading abilities of first-grade students at SD Negeri 68 Palembang. The method used in this research is an experimental study with a quasi-experimental design. The data collection techniques in this study involve tests and documentation, while the data analysis technique uses normality tests, homogeneity tests, and hypothesis testing using an independent simple t-test. Based on the research results, it shows that there is an effect of the syllable method on the early reading abilities of first-grade students, as seen from the hypothesis test results where the significance value is 0.000 < 0.05 and t-count 4.991 > 2.023, meaning Ho is rejected and Ha is accepted. syllable method assisted by flashcard media, reading ability.